ANALISIS PENDIDIKAN KARAKTER DI PAUD HUDAIBIYAH GUNUNG MEDAN (STUDI KASUS) - Desi Karmila; Ana Novitasari; Sudiati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This research is necessitated by the observation that not all Early Childhood Education (PAUD) institutions possess a uniform understanding and consistent application of character education principles. Discrepancies in educators' comprehension, insufficient resources, and the less-than-optimal engagement of parents in supporting children's character development within the home environment are identified as significant factors impacting the efficacy of character education within PAUD settings. Consequently, it is deemed imperative to conduct an in-depth analysis of character education at PAUD Hudaibiyah Gunung Medan. This study aims to meticulously examine the implementation of character education within this specific institution. This qualitative research uses a case study approach with observation and interview techniques to collect data from school principals, teachers, and parents. The results show that PAUD Hudaibiyah Gunung Medan has integrated character education through the Merdeka curriculum and daily habits, focusing on six dimensions of the Pancasila Student Profile: Faith, Piety, and Noble Character; Global Diversity; Mutual Cooperation; Independence; Creativity; and Critical Thinking. Observation results indicate that character education activities are embedded in daily school activities. Interviews confirm that teachers involve parents in character education programs and apply character values through small interactions.